Single Layer Repair of Large Anterior Skull Base Defects without Vascularized Mucosal Flap - Yoo, Frederick; Wang, Marilene B.; Bergsneider, Marvin; Suh, Jeffrey D. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Objectives Bilateral anterior skull base (ASB) defects following endoscopic endonasal tumor resection are most commonly repaired utilizing multilayered reconstruction with a vascularized mucosal flap. Single-layer closure of large ASB defects has been described in the literature but this technique has yet to gain a widespread use. We report our experience with a series of patients who underwent reconstruction of large ASB defects using a single-layer intradural graft, without nasoseptal flaps. We also compared the use of acellular dermal matrix (AlloDerm, LifeCell, Branchburg, New Jersey, United States) or collagen matrix xenograft (Duramatrix, Stryker, Kalamazoo, Michigan, United States) as the graft biomaterial.Design A retrospective case series.Setting Tertiary academic medical center.Main Outcome Measures Postoperative cerebrospinal fluid leak, the number of postoperative debridements, the number of postoperative infections, and time to remucosalization.Results Two patients were reconstructed with AlloDerm and three with Duramatrix, with all patients receiving postoperative external beam radiation. There were no postoperative cerebrospinal fluid leaks identified in these patients during follow-up. The AlloDerm group showed increased postsurgical crusting, the number of clinically apparent postoperative infections, and an increased time to remucosalization.Conclusions Single-layer repair without a vascularized mucosal flap is a viable method of skull base repair for large ASB defects. We found repair with Duramatrix was superior, with less graft crusting and infection, requiring fewer debridements.
Keywords: anterior cranial fossa; skull base; skull base neoplasm; paranasal sinus neoplasms; reconstructive surgical procedures; biocompatible materials